Climate change education in Indonesia’s formal education: a policy analysis - Kelvin Tang (npj Climate Action, 2024)
Abstract This article conducts a comprehensive analysis of climate change education within the framework of climate change policy and education policy in Indonesia. Employing thematic analysis on twenty climate change policy texts, twelve K-12 education policy texts, and seventeen expert interview transcripts, our study explores the congruency of climate change education in both policy domains. Despite the critical need for coordinated policies to optimise the design and implementation of climate change education, the analysis reveals a significant discrepancy between Indonesia’s climate change policy and education policy regarding this crucial aspect. Four key themes emerged: the marginalisation of climate change education, the lack of synergies between relevant policies and stakeholders, the predominant economic values, and the optimistic future outlook. The study also assesses the alignment between Indonesia’s approach and global trends in climate change education. The findings shed light on critical areas for improvement and development in the integration of climate change education within the Indonesian policy landscape.